327 Variation in Management of Spinal Gliobastoma Multiforme: Results From a National Cancer Registry. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Moinuddin, F.M; Alvi, Mohammed A; Wahood, Waseem; Goyal, Anshit; Yolcu, Yagiz Ugur; Bydon, Mohamad
Abstract: INTRODUCTION: Primary glioblastoma of the spinal cord (spinal GBM) is a rare tumor, relative to its cranial counterpart (cranial GBM). Our current knowledge of spinal GBM epidemiology, tumor characteristics, and treatment is insufficient and mostly based on single-institution case series. METHODS: All patients diagnosed with GBM in brain and spinal cord between the years 2004 and 2014 were queried from the National Cancer Database. Chi-square analysis was used to compare presenting characteristics. Kaplan-Meier, Cox regression analyses were employed for survival analyses. RESULTS: In total, data from 103 496 patients with cranial GBM and 190 patients with spinal GBM were analyzed. Overall survival (OS) was not different for patients with spinal GBM when compared to cranial GBM, but the data trended toward significance with cranial GBM have a lower survival ( P  = .07). Kaplan-Meier analysis showed spinal GBM patients had significant better survival in 18 to 65 yr age group than <18 and >65 yr age group ( P  = .003). Patients with spinal GBM who received radiation with or without chemotherapy had a better median survival (14.95 mo) compared with other treatment combinations (surgery alone, 8.87 mo; surgery with adjuvant therapy, 9.33 mo; palliative only, 1.31 mo, P  = .28). On multivariable analysis,  <18 yr age group was associated with improved survival (HR = 0.50, 95% CI 0.23-1.00, P  = .046), while tumor extension was associated with poor survival (HR = 2.71, 95% CI 1.04-6.22, P  = .041). Interestingly, surgery with adjuvant therapy was unable to show increase survival compared to other treatment modalities. CONCLUSION: We found trend of increased survival in patients with spinal GBM compared to cranial GBM. Surgery with adjuvant therapy was found to have no survival benefit for patients with spinal GBM. However, due to its rarity, a multi-institutional, prospective, controlled study is required to define the optimal treatment of spinal GBM.